Exotic snake bites in the Czech Republic—Epidemiological and clinical aspects during 15-year period (1999–2013). (April 2014) - Valenta, Jiri; Stach, Zdenek; Michalek, Pavel
Abstract: Only one natural venomous snake—the adder viper—lives in the central European region and its bite is usually associated only with mild course of envenoming. Cases of envenoming caused by exotic snakes among their breeders are clinically more important. Objective . The aim of this study was to analyze the epidemiological and clinical aspects of registered venomous bites caused by exotic snakes in the Czech Republic over a period of 15 years (1999–2013). Materials and methods. This is an observational case series. Data have been collected retrospectively from a database and medical charts of the Toxinology Center belonging to the General University Hospital in Prague. Results. In total, 87 cases of exotic snakebites caused by 34 venomous snake species were registered during the study period, coming from 18 genera of Elapinae, Viperinae, and Crotalinae subfamilies. In the cohort, 29 patients (33.3%) developed systemic envenoming and 17 (19.5%) were treated with antivenom. Ten cases of envenoming (11.5%) were considered as potentially life threatening. No patient died due to envenoming caused by exotic snake bites during the study period. Four illustrative cases of envenoming ( Echis pyramidum, Dendroaspis polylepis, Protobothrops mangshanensis, and Proatheris superciliaris ) are described in detail. Conclusion. Bites caused by exotic snakes resulted in serious and life-threatening envenomings in some patients. Early transfer to the Center, antivenom administration, and support of failing organ functions contributed to favorable outcome of victims.